KAJIAN KARAKTERISTIK OBJEKTIF DAN SUBJEKTIF TUAK AREN (Arenga pinnata) BERDASARKAN LAMA WAKTU PENYIMPANAN - dhyana putri (Meditory : The Journal of Medical Laboratory, 2017)
Palm tuak is one of the traditional drink that is usually consumed by majority people in Bali. Tuak palm is produced from fermented palm juice. The fermentation process makes sucrose contained in palm juice will turn into alcohol and continues to acetic acid. The aim of this research is to know the characteristic objective and subjective palm tuak (Arenga pinnata) based on the storage time. The method in this research was quasi experiment design. The samples of palm tuak were stored at room temperature (24-30°C) on the first day to fifth day. This research was conducted by measuring characteristics objective and subjective at palm tuak, determination of ethanol's concentration by gas chromatography (GC), determination of the pH by pH stick, determination of total acid by titration method, and organoleptic test by acceptance test method. The results showed that the ethanol content obtained during time storage of first to fifth day are 8,1512%, 8,234%, 9,117%, 10,6214%, dan 11,615% respectively. The pH was determined is 4. While total acid obtained during time storage of first to fifth day are 0,321%, 0,421%, 0,433%, 0,472%, dan 0,480%. The result of organoleptic test palm tuak showed that palm tuak that were stored on the first day are the most preferred among the others in terms of taste, color, and aroma.